Combined dynamic operation of PEM fuel cell and continuous dehydrogenation of perhydro-dibenzyltoluene. (19th October 2021) - Geiling, Johannes; Steinberger, Michael; Ortner, Florian; Seyfried, Roman; Nuß, Andreas; Uhrig, Felix; Lange, Christopher; Öchsner, Richard; Wasserscheid, Peter; März, Martin; Preuster, Patrick
Abstract: Hydrogen storage in liquid organic hydrogen carriers (LOHC) such as the substance system dibenzyltoluene/perhydro-dibenzyltoluene (H0/H18-DBT) offers a promising alternative to conventional methods. In this contribution, we describe the successful demonstration of the dynamic combined operation of a continuously operated LOHC reactor and a PEM (polymer exchange membrane) fuel cell. The fuel cell was operated stable with fluctuating hydrogen release from dehydrogenation of H18-DBT over a total period of 4.5 h, reaching electrical stack powers of 6.6 kW. The contamination with hydrocarbons contained in the hydrogen after activated carbon filtering did not result in any detectable impairment or degradation of the fuel cell. The proposed pressure control algorithm based on a proportional integral (PI) controller proved to be a robust and easy-to-implement approach to enable the dynamic combined operation of LOHC dehydrogenation and PEM fuel cell. Graphical abstract: Image 1 Highlights: Stable operation of fuel cell while fluctuating hydrogen release from LOHC reactor. Demonstration of robust and easy-to-implement control algorithm. Purity analysis of released hydrogen from dehydrogenation of perhydro-dibenzyltoluene. Characterisation of the dynamics of LOHC dehydrogenation and PEM fuel cell.